Identity trends of academics at the Universidade Aberta (Portuguese Open University) - Moreira, Darlinda (2017)
As a result of the European crises, higher education institutions have been affected by dramatic budgets cuts that have repercussions in the quality of education, in the financial support for research, in students support as well as in the faculty’s capacity to promote their own professional development. Moreover advances in communication technology have been radically transforming all the different dimensions of academic life. This chapter presents the analytical perspective of three academic women that belong to the Department of Education and Distance Education in the Portuguese Open Education University and who have lived through the profound transformations in their university that have impact in pedagogical approaches, content and teaching materials, student population, and methodologies.as well as in social adjustments related to: how the national framework of faculty professional development integrates the differences of our institution and how we act before them.